Ancaman Pencerobohan Sistem Berkomputer Dilemmas In Corporate Communication Division Pertindihan Perintah Mahkamah Syariah Panggilan Pulau Besar Pencegahan SARS - Najwa Hayaati Mohd Alwi; Norhayati Rafida Abdul Rahim; Adibah Sulaiman @ Mohamad; Mohd Radhi Ibrahim; Irwan Mohd Subri; Abdul Manan Ismail; Arif Fahmi Md Yusof; Syed Ahmad Tarmizi Syed Omar; Mohd. Fauzi Mohd. Amin (Universiti Sains Islam Malaysia, 2024)
This technical report contains cases, namely "Ancaman Pencerobohan Sistem Berkomputer"; "Dilemmas In Corporate Communication Division"; "Pertindihan Perintah Mahkamah Syariah"; "Panggilan Pulau Besar"; "Pencegahan SARS" and "Justice Delayed: Aida Melly Case". The case "Ancaman Pencerobohan Sistem Berkomputer" presented an issue relating to the ethics in computerise operation environment. "Dilemmas In Corporate Communication Division" looked at the factors in handling public complaints. While "Pertindihan Perintah Mahkamah Syariah" looked at the workings of syariah legal system. The case "Panggilan Pulau Besar" discussed about deviant teachings while the case "Pencegahan SARS" presented crisis management fkom Islamic perspective. The cases have valuable learning points and together with teaching guides, they could be usefbl for teaching-learning purposes. However, it must be noted that the cases are written as case research exercises and they are not meant to evaluate good or bad management practices. Any use of the cases and reference to them must be accompanied with written permission of the author(s) concerned.